Estudo de caso: desgaste nos bocais supersônicos do bico de lança da aciaria BOF - Fabricio Silveira Garajau (2017)
Wear of the supersonic nozzle in tip of lance has been a recurrent problem after a while of operation of the lances in the Vallourec Brazil steelmaking, exiting prematurely, due to the low performance of the supersonic jet after nozzle wear. The understanding of the phenomenaand mechanisms that cause the nozzle wear, can lead to the discovery of new solutions, aiming to reduce the relevance of this type of failure in the life of the tip lance. In the present work a case study will be realized, through a failure analysis in a nozzle in tip of lance of the Vallourec Brazil steelmaking, removed from operation due to wear of the nozzles. The basis of the study will be the metallographic analysis and computationalsimulations for the understanding of the phenomena that provide the nozzle wear. Initially will be presented a bibliographic review the basic operating concepts of the Basic Oxygen Furnace (BOF) converters, as well as their main equipment and process characteristics. In thetheoretical fundamentals chapter, some basic analytics concepts of supersonic nozzle calculations, copper metallurgy, and the basic equations governing Computational Fluid Dynamics (CFD) modeling will be presented. All methodology, materials and criteria used in the failure analyzes, as well as the operational parameters of the nozzle, will be presented in Chapter 5. In this chapter, also will be presented the body conditions, geometry and mesh used in CFD simulations. In Chapter 6, the results of the metallographic analyzes are presented, where the granulometric changes could be correlated with the results of the CFD simulations, aiding in the characterization of the wear mechanism. As main conclusions, it can be verified that in the region of wear occurred the largest grain growth, indicating a higher thermal input in this region. It was observed that during operation with the lowest blow flow, the post-combustion starts inside the nozzles, caused by the jet detachment, and generating temperatures consistent with the grain growth found. So, the wear mechanism can be characterized as the gradual melting of the copper along the heats when operating with the lowest blow flow rate. Thus, the nozzles could be resized, with hope a longer life, because they no longer present post-combustion inside the nozzles during the lower blow flow.